L'obiezione di coscienza nei paesi della Comunità Europea (Atti dell'incontro, Bruxelles - Lovanio, 7-8. dicembre 1990 - Consorzio Europeo di Ricerca sui Rapporti tra Stati e Confessioni Religiose (Università degli Studi di Milano. Facoltà di giurisprudenza. Publicazioni di Diritto Ecclesiastico, 1992)
Artikelverzeichnis: Ergec, Rusen, Les dimension européennes de l'objection de conscience; Duffar, Jean, L'objection de conscience en droit français; Hogan, Gerhard, The refusal to fulfill vertaien obligations imposed by the civil law appialing to the problems of conscience in the countries of the European Community Ireland; Lariccia, Sergio, Conscientious objection in italian law; Loschelder, Wolfgang, The non-fulfillment of legally imposed obgligations because of conflicting decisions of conscience - the legal situation in the Federal Republic of Germany (FRG); Lyall, Francis, Conscience and the law: ik national report; McClean, J. D., Protection of Freedom of conscience in fields other than that of military service; Perrakis, Stelios, L'objection de conscience dans l'ordre juridique hellénique; Prieto Sanchis, Luis, L'objection de conscience en Espagne; Siesby, Erik, Conscientious objection in danish law; Robbers, Gerhard, Rapport de synthèse; Torfs, Rik, L'objection de conscience en belgique; Torfs, Rik, L'objection de conscience dans l'ordre juridique luxembourgeoise; Vermeuelen, Ben. P., Conscientious objection in dutch law